2016
DOI: 10.1016/j.brainres.2015.11.026
|View full text |Cite
|
Sign up to set email alerts
|

5-hydroxytryptamine 1A (5-HT 1A ) receptor agonists: A decade of empirical evidence supports their use as an efficacious therapeutic strategy for brain trauma

Abstract: Traumatic brain injury (TBI) is a significant and enduring health care issue with limited treatment options. While several pre-clinical therapeutic approaches have led to enhanced motor and/or cognitive performance, the benefits of these treatments have not translated to the clinic. One plausible explanation is that the therapies may not have been rigorously evaluated, thus rendering the bench-to-bedside leap premature and subsequently unsuccessful. An approach that has undergone considerable empirical researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 75 publications
(132 reference statements)
2
27
1
Order By: Relevance
“…Previous studies conducted in our laboratory evaluating continuous EE exposure together with chronic administration of the 5-HT 1A receptor agonists 8-OH-DPAT and buspirone also did not reveal greater effects of combinational therapies on neurobehavioral and cognitive endpoints. 11,28,29 Moreover, Perry and coworkers 52 also reported a similar ceiling effect after enrichment exposure that precluded a synergistic effect in combination with MPH. Specifically, rats reared in an enriched housing condition showed higher mean adjusted delay scores (i.e., reduced impulsive choice) in a delay discounting task compared with rats reared in an isolated condition.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies conducted in our laboratory evaluating continuous EE exposure together with chronic administration of the 5-HT 1A receptor agonists 8-OH-DPAT and buspirone also did not reveal greater effects of combinational therapies on neurobehavioral and cognitive endpoints. 11,28,29 Moreover, Perry and coworkers 52 also reported a similar ceiling effect after enrichment exposure that precluded a synergistic effect in combination with MPH. Specifically, rats reared in an enriched housing condition showed higher mean adjusted delay scores (i.e., reduced impulsive choice) in a delay discounting task compared with rats reared in an isolated condition.…”
Section: Discussionmentioning
confidence: 94%
“…14,[22][23][24][25][26][27][28][29][30][31][32]35 Concurrently, many other therapeutic interventions have also been reported to enhance behavioral outcome after TBI using various pre-clinical models; [9][10][11][12][13][14][15][16][17][18] however, most of these strategies have not successfully translated from the bench to the bedside. 19,20 While numerous factors may account for the lack of translation, one salient reason may be the use of single therapies for a disease that exhibits multiple pathophysiological events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different outcomes may be attributed to the mechanism of action in that quetiapine is a weaker D 2 receptor antagonist and aripiprazole is a D 2 receptor agonist and a 5-HT 1A partial agonist. Studies from our laboratory have shown that various pharmacotherapies with these mechanisms of action benefit functional recovery after TBI (for excellent reviews see Bales et al, 2009; Bondi et al, 2015; Cheng et al, 2016), and thus suggest that patients can be treated efficiently for TBI-induced agitation and aggression without restricting their ability to recover spontaneously after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…These include pharmacological, steroidal, anti-inflammatory, cellular replacement, and behavioral methods. [1][2][3][4][5] Although a number of compounds have been tested in phase 3 clinical trials, none have proven to be efficacious at significantly improving outcomes. Advances in technology bring forth new treatment options that are being readily explored in experimental and clinical settings.…”
Section: Introductionmentioning
confidence: 99%